El periplo norteafricano de Ofelas - Mederos Martín, Alfredo (Gerión. Revista de Historia Antigua, 2006)
The atlantic periplus of Ophelas could be have realized to instance of Alexander, ca. 331-323 BC, to evaluate the carthaginian presence in the North African Atlantic facade, before his projected campaign against Carthage and later try to reach the Columns of Herakles by the African coast. A second possibility could be during the period of Ophelas as governor of Cyrene, between 322 and 312 BC, before the preparations of his campaign against Carthage the 308 BC, to seek information on the destination points of the land caravans that were transporting gold powder until the North African Atlantic facade. The policy of Ophelas as governor had as priority the control of the land route of the gold, ivory, animal skins, ostrich pens, slaves, etc. that was arriving from the Chad lake by the Oasis of Dschofra and the desert of Fezzan. His objective was diverted the trade progressively toward Alexandria, in detriment from Carthage, after obtaining to relocate the frontier between Egypt and Carthage in the Euphrantas Tower, current region of the Syrtis, displacing some 150 km. westward the ancient limit between Carthage and the Cyrenaean in the arae Philaenorum.
Keywords: Periplus; Ophelas; Cyrene; Atlantic; Gold trade; Carthage; Hanno; Himilco